Rare Spigelian Hernia in a Young Adult: Clinical Presentation, Diagnosis, Surgical Management, and Review of the Literature (JBN (Jurnal Bedah Nasional), 2026)
Background: Spigelian hernia is a rare type of ventral hernia, occurring through the Spigelian aponeurosis at the linea semilunaris. It typically presents in patients aged 40–70 years, with a higher frequency on the right side. Diagnosis is often delayed due to its subtle symptoms and location, making it a challenge to detect early. Objective: This case report aims to describe a rare instance of Spigelian hernia in a 28-year-old male, highlighting the clinical presentation, diagnostic process, and management approach. Case Report: A 28-year-old male mechanic presented with a right lower abdominal bulge, which increased in size upon physical exertion, such as during sit-ups or when coughing. Initial physical examination revealed a palpable, reducible mass in the right lower abdomen. Imaging confirmed the presence of a Spigelian hernia. Conclusion: Spigelian hernia, while rare, should be considered in young patients presenting with abdominal bulges, especially when accompanied by intermittent pain and activity-induced exacerbation. Early diagnosis and surgical intervention are essential to prevent complications such as incarceration or strangulation.